Analisis Kesiapan Kerja Siswa Sekolah Menengah Kejuruan Jurusan Teknik Instalasi Tenaga Listrik - Ridho Irawan; Hendri Hendri (Jurnal Pendidikan Teknik Elektro, 2022)
The purpose of this study is to describe and analyze the work readiness of students at SMKN 2 Lubuk Basung Department of Electrical Power Installation Engineering. Work readiness refers to an individual's total physical, mental, and life experience, as well as their willingness and capacity to perform work or an activity. The research method used in this research is descriptive research method with a quantitative approach. The variable studied was the work readiness of students majoring in Electrical Power Installation Engineering, SMKN 2 Lubuk Basung. The variable studied was the work readiness of students majoring in Electrical Power Installation Engineering, SMKN 2 Lubuk Basung. The research instrument used in this study was in the form of a questionnaire which was distributed to respondents directly which had 1 variable and 7 indicators. This research questionnaire was conducted on students in class XII Electrical Power Installation Engineering with a total of 31 respondents and the results obtained were 15 respondents with poor work readiness results. The results of this study can be concluded that the work readiness of students majoring in Electrical Power Installation Engineering, SMKN 2 Lubuk Basung is categorized as bad.